2018
DOI: 10.1108/ijsi-03-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fatigue limit improvement in needle peened welded joints containing crack-like defects

Abstract: Purpose The purpose of this paper is to estimate the acceptable defect size amax after needle peening (NP) and predict the fatigue limit improvement through the use of NP for an austenitic stainless steel welded joint containing an artificial semi-circular slit on a weld toe. Design/methodology/approach Residual stress and hardness distribution were measured. Microstructures around the weld toe were observed to clarify the cause for the change in hardness after NP. Finite element method analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Previous studies [14,15] reported that the stress concentration of the weld toe was reduced after NP for welded joints and indicated a high stress concentration factor of K t of W, which was more than 2.0. However, notably, the stress concentration of the welded joint can increase after NP if a small NP is applied for the welded joint stress concentration at the weld toe.…”
Section: Finite Element Analysis Of the Stress Concentration Of The Wmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies [14,15] reported that the stress concentration of the weld toe was reduced after NP for welded joints and indicated a high stress concentration factor of K t of W, which was more than 2.0. However, notably, the stress concentration of the welded joint can increase after NP if a small NP is applied for the welded joint stress concentration at the weld toe.…”
Section: Finite Element Analysis Of the Stress Concentration Of The Wmentioning
confidence: 92%
“…As shown in Figure 4c, the diameter (2a) to depth (a) ratios in mm were 2.0/1.0 and 3.0/1.5. The slit size was determined based on the results of previous studies [13,15], which found the acceptable defect size after NP. The aperture width of the slit was approximately 0.1 mm.…”
Section: Needle Peening and The Introduction Of The Surface Defectmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследования авторов (Melaku, & Jung, 2017;Fueki, & Takahashi, 2018) также направлены на прогнозирование усталостной долговечности сварных соединений при помощи численного моделирования. Однако предлагаемые расчетные модели учитывали не только особенности нагружения конструкции и геометрию сварного шва, но и остаточные напряжения от сварки.…”
Section: Introductionunclassified
“…Takahashi et al showed that the value of ac could be increased by the compressive residual stress induced by shot peening [3,4]. The values of ac depend on the distribution of residual stress.…”
Section: Introductionmentioning
confidence: 99%